Innovation and productivity under nationalisation : the first thirty years - Harlow, Christopher (London : George Allen & Unwin Ltd., 1977)
The core of this book consists of five main chapters. Each one deals with a different British public corporation and examines the way in which the corporation has introduced technical change in its capital equipment over a period of approximately thirty years. The organizations chosen for the study were: 1) the National Coal Board; 2) the British Gas Corporation (formerly Gas Council and Area Gas Boards); 3) the European branch of British Airways (formerly British European Airways); 4) the Central Electricity Generating Board (formerly the generation and transmission division of the Central Electricity Authority); and 5) the telecommunications service of the Post Office.
Includes bibliographical references and index.
ne 3/04/2018
Loans
Keywords: Technological innovations; Government business enterprises